2012
DOI: 10.3138/cmlr.1103
|View full text |Cite
|
Sign up to set email alerts
|

Health Communication and Psychological Distress: Exploring the Language of Self-harm

Abstract: This study explores adolescents' accounts of self-harm with a view to elucidate the implications for health care practitioners seeking to administer care to teenagers in English. Drawing on a corpus of 1.6 million words from messages posted on a UK-hosted adolescent health Web site, analysis began by identifying a range of keywords relating to self-harm. The subsequent contextual examination of these keywords afforded a close description of the contributors' experiences of self-harm and the factors that result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In recent a corpus-assisted research study, Harvey and Brown (2012) reported on an examination of adolescents' linguistic formulations of self-harm concerns in the AHEC. As the list of mental-health-related keywords derived from this corpus (appearing in Table 9.1 in the previous section) attests, a number of the most salient keywords in the corpus relate to the topic of self-harm.…”
Section: Study 2: Expressing Concerns About Self-harm Onlinementioning
confidence: 99%
“…In recent a corpus-assisted research study, Harvey and Brown (2012) reported on an examination of adolescents' linguistic formulations of self-harm concerns in the AHEC. As the list of mental-health-related keywords derived from this corpus (appearing in Table 9.1 in the previous section) attests, a number of the most salient keywords in the corpus relate to the topic of self-harm.…”
Section: Study 2: Expressing Concerns About Self-harm Onlinementioning
confidence: 99%
“…indeed emerge from this type of research. Addiction themes have been observed in 3.4–41.7% of posts to NSSI message boards, ( Whitlock et al, 2006 ), 10.8% of posts to NSSI groups on Facebook ( Niwa & Mandrusiak, 2012 ), and many NSSI-related messages sent from teens to health professionals ( Harvey & Brown, 2012 ). Posters would frequently solicit help for their “addiction” to NSSI or celebrate anniversaries or lengths of time free from NSSI, much like individuals in recovery from SUD.…”
Section: Introductionmentioning
confidence: 99%
“…The final summary in this literature review of keyword studies of adolescent healthcare interaction is a study by Harvey and Brown (2012), who investigated adolescents' experiences of self-harm in a corpus of messages taken from the Teenage Health Freak website between 2004-2008. The study follows the same steps as Harvey et al ( 2008) outlined above: a keyword extraction was performed using the BNC as comparative corpus, which was followed by semantic categories being assigned to the keywords.…”
Section: Commentarymentioning
confidence: 99%
“…The words specific to self-harm were identified and their collocations explored in the corpus. Harvey and Brown (2012) find that their analysis reveals several patterns and commonalities in adolescents' accounts of self-harm, information which provide important insights for health professionals into what drives rising numbers of young people to self-harm.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation